PENGARUH KOMPOSISI TIM UJI TRAMPIL DAN KEPUASAN KERJA TERHADAP KINERJA KOLATARMABAR - Darwin Sagala (Jurnal Manajemen Pendidikan, 2016)
The objective research is to obtain information concerning effect capability tester team composition and job satisfaction toward Job performance or outcomes Indonesian navy western fleet exercise command. The research was conducted by using survey method with path analysis in testing hypothesis.In this research 90 from 100 personel Indonesian navy western fleet exercise command selected random sampling.The research was focused on three aspect : composition team and job satisfaction toward outcomes. The data were collected with questionare and analyzed with path analysis result on the analysis it is calculated that (1) there the positive direct effect of team composition toward job satisfaction (2) there is the positive job satisfaction toward outcomes (3) there is positive direct effect of team composition toward outcomes.